STRUCTURE OF PROFESSIONAL COMPETENCY OF THE CHAIRMAN GENERAL EDUCATIONAL INSTITUTION: THEORETICAL ASPECTS - Degtyareva, O. A. (Problems of Engineer-Pedagogical Education, 2018)
The article analyzes the scientific researches of the concepts "competence", "professional competence" and theoretical aspects of the development of professional competence of the general educational institutions leaders. On the basis of analysis and synthesis of scientific articles the concept of "professional competence of the comprehensive educational institution leader" is determined. The scientific and theoretical substantiation of the structure definition of the comprehensive educational institution leader professional competence is carried out. The leader professional competence is considered by the author as an integral characteristic, which reflects a set of essential features (qualities / characteristics) inherent in the manager personality which are identified in two components - general (universal) and special (professional) competencies. Conclusions regarding the expediency of developing and introducing a technology for evaluating the leader professional competence of general educational institutions according to the results of the advanced training are made